The Effects of Immediate and Delayed Corrective Feedback on the Acquisition of English Subject-Verb Agreement by EFL Learners - Yalda Moslemi; Shirin Abadikhah; Baqer Yaqubi (Journal of English Language Teaching and Learning, 2023)
The timing of corrective feedback (CF) provision has been a controversial issue in SLA research. Despite widespread research, there is still disagreement on whether the erroneous structures should be addressed immediately or at a delayed time after task completion. This study investigates the comparative effects of immediate and delayed feedback on developing subject-verb (s-v) agreement by Iranian EFL learners. To this end, 28 university students were divided into immediate (n=14) and delayed (n=14) CF groups after the administration of the Oxford Placement Test. The study involved a pre-test, three treatment sessions and a post-test. The two feedback groups received treatments followed by either immediate feedback provided after task completion or delayed feedback delivered after 3 days of task completion. The tests and treatments contained various activities including multiple-choice, cloze, fill-in-the-blanks and picture description task. The results of the analysis of test scores on the pre- and post-tests were indicative of the outperformance of the immediate CF group, implying that the immediate feedback may be more beneficial for developing s-v agreement accuracy than delayed feedback. The findings of this investigation can bear efficient implications for language teachers and researchers.